Perceptions of Brand Management in - Mawela, Tendani (My University, 2011)
The non-profit sector faces a myriad of challenges. Non Profit Organisations (NPOs) operate in a highly competitive market for financial support, skilled employees and volunteers. They are thus often driven to adopt commercial practices to improve their strategic performance and differentiate themselves in an environment that has experienced significant growth and currently has vibrant and active NPO sectors across the various continents. The study reviewed the application of brand management within the South African NPO sector and aimed to establish the understanding of the branding construct, the main drivers of a brand and the objectives of branding within this sector. The research paradigm was qualitative and the study was exploratory in nature applying input from thirteen in-depth interviews with respondents from the NPO sector. A thematic approach to qualitative data analysis was applied and the themes that arose included the terminology in use in the NPO sector, how the brand construct is understood, the elements of a brand, challenges in branding, the management and ownership of NPO brands and the results of undertaking branding. The study established that South African NPOs have different goals in branding with the majority seeking to increase visibility and credibility and garner support for their cause. There are varying understandings of the concept of a brand and it is deduced that branding is still in its infancy in the sector. NPOs also offered a variety of drivers that are deemed to be important for the development and maintenance of a brand supporting the notion that branding is multifaceted and complex. Furthermore, funding was overwhelmingly highlighted as the major constraint for brand management activities followed closely by access to the right skills and knowledge in this area. These key issues highlighted the need for a branding approach that is both relevant and accessible to the NPO sector bearing in mind their daily challenges. The study includes recommendations for key stakeholders and proposes a structure for an NPO branding information source. Proposals for future research are also highlighted.
MBA - WBS
Keywords: Brands and branding; Brand management; Non-profit sector